Whose America? Decolonial Translation by Frederick Douglass and Caetano Veloso - Price, Joshua (TTR)

(untitled) (Association canadienne de traductologie, 2015)
Colonial domination entails a struggle over interpretation. The colonizers establish whose version of reality will be codified and become the dominant one. Breaking with that dominant, authorized account implies a struggle against hegemony. Translators have always played key roles in colonization as agents of the colonizer. Subaltern translators and interpreters have often served in this role. But they often contest dominant meanings. They subvert dominant meanings as they transform them across the colonial divide. Theorizing translation practices from that point of colonial conjunction or contact, this essay adduces two examples to see how a decolonial methodology to study translation and power can shed light on how, in the hands of an astute translator, a translation can offer a counter-narrative that deconstructs colonial systems of meaning. The two examples: Frederick Douglass’ intralingual translation of the meaning of the Fourth of July (1852) and singer Caetano Veloso’s recording of Augusto de Campos’ translation (1979) of John Donne’s “Elegy 19: To His Mistress Going To Bed” (1654). Three interconnected characteristics make the translations decolonial. (1) They are abusive (Lewis, 2000; Venuti, 2013). (2) The target language or culture is an imagined world, better and more just than the world we live in now (Santos, 2014). (3) They are performatives insofar as they begin to bring that imagined world into existence through performing the translation (Austin, 1975). As a deconstructive embrace, this kind of translation draws attention to the colonial legacy and to the colonial context, and also to itself—that is, to its own selective appropriation (Spivak, 1995, p. 31).